Uji Antagonistik Bakteri Penghasil Indole Acetic Acid Terhadap Jamur Helminthosporium maydis Secara In Vitro - TAMPUBOLON, HELENA; KHALIMI, KHAMDAN; PHABIOLA, TRISNA AGUNG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2023)
Antagonistic Test of  Indole Acetic Acid  Producing Bacteria Against  Helminthosporium   maydis  In Vitro Helminthosporium maydis is the cause of important diseases in maize, including leaf blight. Leaf blight is the most dominant disease because it causes large losses. The use of biological agents is one way to treat leaf blight that is environmentally friendly. One of these biological agents is IAA-producing bacteria. This research was conducted  in vitro . The results showed that there were several IAA-producing bacteria that were able to inhibit the growth of  H. maydis  in vitro with the highest inhibition in the treatment of  B. thuringiensis  GR12 isolates of 96.44% when compared to controls. IAA-producing bacteria were able to inhibit the growth of H. maydis biomass with the percentage of inhibition ranging from 73.97% - 80.82%. The treatment of IAA-producing bacterial filtrate at a concentration of 20%-90% was able to inhibit the growth of  H. maydis  colonies in vitro. The results of this study indicate that IAA compounds produced by bacteria are antifungal.